1996
DOI: 10.1002/ana.410390305
|View full text |Cite
|
Sign up to set email alerts
|

Human α‐tocopherol transfer protein: Gene structure and mutations in familial vitamin E deficiency

Abstract: Familial vitamin E deficiency (AVED) causes ataxia and peripheral neuropathy that resembles Friedreich's ataxia. AVED is thought to be caused by a defect in the transport of vitamin E in liver cells, which is the probable function of alpha-tocopherol transfer protein (alphaTTP). We have cloned the cDNA and several genomic phage clones covering the entire human alphaTTP gene and determined the junctions between the five exons and four introns that composed the gene for human alphaTTP. Three mutations in three u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
60
0
4

Year Published

1997
1997
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(66 citation statements)
references
References 11 publications
2
60
0
4
Order By: Relevance
“…Ttpa Ϫ/Ϫ mice at 18 months of age had no obvious signs of neurological disease. In contrast, humans with ␣-TTP gene defects develop ataxia with vitamin E deficiency by the first decade of life (16)(17)(18). This discrepancy may reflect species differences in the susceptibility of the nervous system to vitamin E deficiency (31).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ttpa Ϫ/Ϫ mice at 18 months of age had no obvious signs of neurological disease. In contrast, humans with ␣-TTP gene defects develop ataxia with vitamin E deficiency by the first decade of life (16)(17)(18). This discrepancy may reflect species differences in the susceptibility of the nervous system to vitamin E deficiency (31).…”
Section: Resultsmentioning
confidence: 99%
“…Although the mechanism is unknown (15), ␣-TTP is believed to selectively transfer ␣-tocopherol from lipoproteins taken up by hepatocytes via the endocytic pathway to newly secreted lipoproteins, which facilitate its delivery to peripheral tissues (12). Humans with ␣-TTP gene defects have extremely low plasma ␣-tocopherol concentrations and develop severe neurodegenerative disease unless they are treated with high doses of vitamin E (16)(17)(18).…”
mentioning
confidence: 99%
“…2B). The TTP(R192H) mutant, however, is associated with a mild late-onset form of heritable vitamin E deficiency in humans (48), and the protein's biochemical activities in vitro are very similar to those of the wild-type protein (18). We found that the intracellular localization of the protein and its response to ␣-tocopherol treatment are indistinguishable from the wild-type protein (Fig.…”
Section: Resultsmentioning
confidence: 72%
“…Ben Hamida et al 6 localizaram o gen da deficiência de vitamina no cromossomo 8q em duas famílias com consangüinidade. A estrutura do gen TTP1 (tocopherol transporting protein 1) e outras mutações associadas à deficiência familial de vitamina E foram posteriormente descritas 37 .…”
Section: Ataxia De Friedreichunclassified